Dari Pembelajaran Organisasional menuju Universitas Korporat: Sebuah Tinjauan Bibliometrik Global dan Model Kontingensi Corporate University di Indonesia - Muh. Asdig Fanani; Irna Dwi Wahyuni; Eliza Deis Widoputri; Reggina Putri Oktarisa (JOM, 2026)
This study examines the fragmentation of scholarly discourse on organizational learning in the public sector and the limited attention given to bureaucratic barriers faced by developing countries in responding to the challenges of the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) and BANI (Brittle, Anxious, Nonlinear, and Incomprehensible) eras. By bridging global developments in organizational learning studies with the specific complexities of Indonesian bureaucracy, this research employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol, complemented by bibliometric analysis of 60 Scopus-indexed publications from 1995 to 2026. The findings reveal a paradigmatic shift from conventional organizational learning approaches toward adaptive performance-oriented models. Furthermore, this study identifies six major dimensions of barriers affecting public sector learning transformation: policy, organizational structure, institutional culture, governance capacity, technological readiness, and psychological factors. Based on these findings, the study proposes the “Indonesian Corporate University (CorpU) Contingency Model,” which integrates regulatory alignment, cultural transformation, and strategic adaptability as key pillars for strengthening organizational learning capacity. Theoretically, this research extends the application of Contingency Theory within public sector knowledge management by emphasizing contextual alignment between organizational design and environmental complexity. Practically, it offers a strategic roadmap for government institutions to develop sustainable and resilient learning ecosystems in the face of continuous bureaucratic transformation.